Feasibility of a Hydraulic Power Assist System for Use in Hybrid Neuroprostheses - Kevin M. Foglyano; Rudi Kobetic; Curtis S. To; Thomas C. Bulea; John R. Schnellenberger; Musa L. Audu; Mark J. Nandor; Roger D. Quinn; Ronald J. Triolo (Applied Bionics and Biomechanics, 2015)
Feasibility of using pressurized hydraulic fluid as a source of on-demand assistive power for hybrid neuroprosthesis combining exoskeleton with functional neuromuscular stimulation was explored. Hydraulic systems were selected as an alternative to electric motors for their high torque/mass ratio and ability to be located proximally on the exoskeleton and distribute power distally to assist in moving the joints. The power assist system (PAS) was designed and constructed using off-the-shelf components to test the feasibility of using high pressure fluid from an accumulator to provide assistive torque to an exoskeletal hip joint. The PAS was able to provide 21 Nm of assistive torque at an input pressure of 3171 kPa with a response time of 93 ms resulting in 32° of hip flexion in an able-bodied test. The torque output was independent of initial position of the joint and was linearly related to pressure. Thus, accumulator pressure can be specified to provide assistive torque as needed in exoskeletal devices for walking or stair climbing beyond those possible either volitionally or with electrical stimulation alone.